Guidance for the Management of Patients with Vascular Disease or Cardiovascular Risk Factors and COVID-19: Position Paper from VAS-European Independent Foundation in Angiology/Vascular Medicine - Gerotziafas, Grigoris T.; Catalano, Mariella; Colgan, Mary-Paula; Pecsvarady, Zsolt; Wautrecht, Jean Claude; Fazeli, Bahare; Olinic, Dan-Mircea; Farkas, Katalin; Elalamy, Ismail; Falanga, Anna; Fareed, Jawed; Papageorgiou, Chryssa; Arellano, Rosella S.; Agathagelou, Petros; Antic, Darco; Auad, Luciana; Banfic, Ljiljana; Bartolomew, John R.; Benczur, Bela; Bernardo, Melissa B.; Boccardo, Francesco; Cifkova, Renate; Cosmi, Benilde; De Marchi, Sergio; Dimakakos, Evangelos; Dimopoulos, Meletios A.; Dimitrov, Gabriel; Durand-Zaleski, Isabelle; Edmonds, Michael; El Nazar, Essam Abo; Erer, Dilek; Esponda, Omar L.; Gresele, Paolo; Gschwandtner, Michael; Gu, Yongquan; Heinzmann, Mónica; Hamburg, Naomi M.; Hamadé, Amer; Jatoi, Noor-Ahmed; Karahan, Oguz; Karetova, Debora; Karplus, Thomas; Klein-Weigel, Peter; Kolossvary, Endre; Kozak, Matija; Lefkou, Eleftheria; Lessiani, Gianfranco; Liew, Aaron; Marcoccia, Antonella; Marshang, Peter; Marakomichelakis, George; Matuska, Jiri; Moraglia, Luc; Pillon, Sergio; Poredos, Pavel; Prior, Manlio; Salvador, David Raymund K.; Schlager, Oliver; Schernthaner, Gerit; Sieron, Alexander; Spaak, Jonas; Spyropoulos, Alex; Sprynger, Muriel; Suput, Dusan; Stanek, Agata; Stvrtinova, Viera; Szuba, Andrzej; Tafur, Alfonso; Vandreden, Patrick; Vardas, Panagiotis E.; Vasic, Dragan; Vikkula, Miikka; Wennberg, Paul; Zhai, Zhenguo; Scientific Reviewer Committee; Bikdeli, Behnood; Guo, Yutao; Harenberg, Job; Hu, Yu; Lip, Gregory Y. H.; Roldan, Vanessa (Thrombosis and Haemostasis, 2020)
COVID-19 is also manifested with hypercoagulability, pulmonary intravascular coagulation, microangiopathy, and venous thromboembolism (VTE) or arterial thrombosis. Predisposing risk factors to severe COVID-19 are male sex, underlying cardiovascular disease, or cardiovascular risk factors including noncontrolled diabetes mellitus or arterial hypertension, obesity, and advanced age. The VAS-European Independent Foundation in Angiology/Vascular Medicine draws attention to patients with vascular disease (VD) and presents an integral strategy for the management of patients with VD or cardiovascular risk factors (VD-CVR) and COVID-19. VAS recommends (1) a COVID-19-oriented primary health care network for patients with VD-CVR for identification of patients with VD-CVR in the community and patients' education for disease symptoms, use of eHealth technology, adherence to the antithrombotic and vascular regulating treatments, and (2) close medical follow-up for efficacious control of VD progression and prompt application of physical and social distancing measures in case of new epidemic waves. For patients with VD-CVR who receive home treatment for COVID-19, VAS recommends assessment for (1) disease worsening risk and prioritized hospitalization of those at high risk and (2) VTE risk assessment and thromboprophylaxis with rivaroxaban, betrixaban, or low-molecular-weight heparin (LMWH) for those at high risk. For hospitalized patients with VD-CVR and COVID-19, VAS recommends (1) routine thromboprophylaxis with weight-adjusted intermediate doses of LMWH (unless contraindication); (2) LMWH as the drug of choice over unfractionated heparin or direct oral anticoagulants for the treatment of VTE or hypercoagulability; (3) careful evaluation of the risk for disease worsening and prompt application of targeted antiviral or convalescence treatments; (4) monitoring of D-dimer for optimization of the antithrombotic treatment; and (5) evaluation of the risk of VTE before hospital discharge using the IMPROVE-D-dimer score and prolonged post-discharge thromboprophylaxis with rivaroxaban, betrixaban, or LMWH.
Keywords: COVID-19; cardiovascular disease; peripheral artery disease; deep vein thrombosis; antithrombotic; antiplatelets; anticoagulants; low-molecular-weight heparin; DOAC